2005
DOI: 10.1002/lt.20472
|View full text |Cite
|
Sign up to set email alerts
|

Tumor size predicts vascular invasion and histologic grade: Implications for selection of surgical treatment for hepatocellular carcinoma

Abstract: H epatic resection and liver transplantation are aggressive, extirpative approaches to the treatment of selected patients for hepatocellular carcinoma (HCC) and are the only known potentially curative treatment options for this disease. Resection and transplantation are largely complimentary, not competing, treatments-resection for patients with preserved liver function and transplantation for patients with compromised liver function. Within each group, selection of patients for surgical therapy is currently b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

46
470
9

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 588 publications
(525 citation statements)
references
References 34 publications
46
470
9
Order By: Relevance
“…A survival analysis was done for 1073 cases, which indicated the relations between tumor size and prognosis, that is, the bigger tumor size, the more probable coexistence of vessel invasion, and the lower tumor grade (Pawlik et al, 2005). We think that the tumor size can reflect on patients liver storage ability and limit surgical-related factors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A survival analysis was done for 1073 cases, which indicated the relations between tumor size and prognosis, that is, the bigger tumor size, the more probable coexistence of vessel invasion, and the lower tumor grade (Pawlik et al, 2005). We think that the tumor size can reflect on patients liver storage ability and limit surgical-related factors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Such cases were suitable for receiving curative treatment such as surgical resection or radiofrequency ablation, although the actual indication depended also on the liver function reservoir of each patient [21,22]. Shorter surveillance intervals did not provide further advantages in terms of tumor size (15.8 ± 5.5 mm with 6-month interval and 16.5 ± 6.4 mm with shorter interval).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified that tumor size and pathological grade are correlated with microvascular invasion. [13][14][15] The risk of vascular invasion and poor prognosis that can be predicted increases with tumor size.…”
mentioning
confidence: 99%